Research On Awareness Of Hospital Managers About Chronic Diseases And The Care By Multidisciplinary Teams Towards Sustainable Health Care Services In Vietnam - Hayashi, Yumiko (2012)

(untitled)
This study focused on top management in health care services in Vietnam.